(untitled) (Open Academia: Journal of Scholarly Research, 2024)
After the pandemic, telemedicine came to the fore in the world. It also paved the way for the practical application of telemedicine. In endocrinology, thyroid diseases are most suitable for the use of telemedicine, hence the term "telethyroidology". In this review, we discuss the use of telemedicine for specific thyroid disorders such as hypothyroidism (subclinical and overt), thyrotoxicosis, thyroid nodules, thyroid cancer, and pregnancy-related thyroid disorders. "Telethyroidology" includes a multidisciplinary approach involving telemedicine diagnostics, teleradiology and telecytopathology, short-term evaluation of patients who need personal consultation, post-thyroidectomy care, as well as long-term monitoring. Adoption of telethyroidology can reduce the in-person consultation burden for endocrinologists, while ensuring that their expertise is accessible to all—resulting in improved diagnosis, treatment, and compliance in thyroid disease